Incorporating sustainable practice in mechanics of structures and materials : proceedings of the 21st Australian Conference on the Mechanics of Structures and Materials, Melbourne, Australia, 7-10 December 2010 /: proceedings of the 21st Australian Conference on the Mechanics of Structures and Materials, Melbourne, Australia, 7-10 December 2010. (©2011) - Unknown
No abstract available